2016
DOI: 10.1002/brb3.618
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cardiovascular risk factors in people with epilepsy

Abstract: ObjectivesEpilepsy has been associated with cardiovascular comorbidity. This study aimed to assess the potential association between cardiovascular risk factors (CRFs), antiepileptic drugs (AEDs), and etiology.Material and MethodsA single‐center retrospective epilepsy cohort from the decade of 2004–2013 was assessed. Poisson regression models with robust variance were estimated to obtain CRF prevalence ratios (PR) according to AED prescription and etiology.ResultsAfter excluding patients in the monotherapy gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…In the same way, age was associated with the presence of dyslipidemia (28) and HTN (29). The association found between epilepsy and dyslipidemia is consistent with the known effect on lipids from treatment with certain anti-epileptic drugs (30, 31).…”
Section: Discussionsupporting
confidence: 85%
“…In the same way, age was associated with the presence of dyslipidemia (28) and HTN (29). The association found between epilepsy and dyslipidemia is consistent with the known effect on lipids from treatment with certain anti-epileptic drugs (30, 31).…”
Section: Discussionsupporting
confidence: 85%
“…These acute effects are likely to be induced by inhibition of voltage-gated sodium and calcium channels with subsequent decrease of cardiac contractility and SV [for review see e.g., (95)]. Probably the most common effects of anti-seizure agents on BP are of indirect nature and related to weight gain [e.g., upon intake of valproic acid, gabapentin, and pregabalin (6)] and detrimental effects on circulating cardiovascular risk factors such as dyslipidemia and hyperhomocysteinemia mostly caused by enzyme-inducing anti-seizure drugs (e.g., carbamazepine, phenobarbital, phenytoin) which in turn may lead to atherosclerosis with decreased blood vessel flexibility and reactivity (9698). A minor subgroup of cases with sudden death may be explainable due to genetic overlaps with genetically caused cardiac arrhythmias and epilepsy, e.g., by mutations in potassium channel genes KCNQ1 and KCNH2 or sodium channel genes SCN5A (99).…”
Section: Interictal Alterations Of Blood Pressure and Baroreflex In Ementioning
confidence: 99%
“…Studies show that epileptic patients have a higher risk of comorbidities including dyslipidemia [10,30], which is a risk factor of cardiovascular disease. One of the risk factors of dyslipidemia can be antiepileptic treatment, but it cannot be clearly determined which kind of medication (drugs and drug combinations) has the greatest impact [31].…”
Section: Discussionmentioning
confidence: 99%
“…One of them, the California Health Interview Survey, concluded that the eating behavior and physical tness in epilepsy are similar to these of healthy people [28]. In contrast, some evidence shows that epilepsy may increase overweight and obesity, as well as the risk of cardiovascular diseases [10]. The percentage of overweight and obesity measured in our study was 53.4% for epilepsy patients and 52.8% for healthy controls, which was similar to another study where this percentage was 55.2% [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation